Komputerisasi dalam Manajemen Perusahaan - Octaviana, Keren Ruyanda; Sarimolle, Frencis Matheos (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The Internship Program organized by the Campus aims to provide students with experience to apply the knowledge they have learned during college in the real world of work. This program is expected to be carried out properly and can overcome and resolve problems that exist in the real world and the world of work. In addition, it adds experience in the world of work and trains students to be disciplined and responsible for the work given to male and female students. In carrying out obligations as students, responsibility is required to carry out tasks as students to complete tasks given in the workplace, and complete and behave well in the workplace.